A hybrid Protection Scheme based on Deep Reinforcement Learning - Kordowich, Georg; Jaworski, Michael; Lorz, Tobias; Scheibe, Christian; Jäger, Johann (2022 IEEE PES Innovative Smart Grid Technologies Conference Europe (ISGT-Europe), 2022)
The growth of distributed renewable energy re-sources pushes classic protection schemes to their limits. An automated workflow is necessary to handle the volatility of future power systems characterized by constantly changing network states. Therefore a hybrid, deep reinforcement learning based protection scheme is proposed in this paper, which combines a single agent training for central protection with a multi agent training for a decentralized fallback.For this purpose, a training framework using a combination of PowerFactory and Python-Scripts connected via a Shared Memory is developed. The framework is used to train agents using Deep Recurrent Q-Learning. First a central protection is trained, which can then be imitated by decentral agents using only local measurements. Tests of the setup show a fast and selective response, which proves that deep reinforcement learning can indeed automatically generate a protection scheme fulfilling high requirements of dependability and security.<br

Das proaktive Überlastschutzsystem - Jaworski, Michael; Jäger, Johann (10. ETG-/FNN-Tutorial Schutz- und Leittechnik, 2018)

Distance Protection Algorithm based on alpha/beta/0-components and Delta Quantities for Getting Insensitive against Power Swings - Jaworski, Michael; Jäger, Johann; Lorz, Tobias (The 15th IET International Conference on Developments in Power System Protection, 2020)
The stabilisation of the distance protection function against inappropriate trip responses due to power swings represents the main topic of this paper. In today's power grids, this problem is covered by the implementation of power swing blocking functions. However, this function is only a corrective add-on algorithm and not an integral part of the distance function itself. This leads to the fact, that symmetrical short-circuits followed up by a power swing are subjected to strongly reduced backup protection dependability from the upstream distance relays. The aim of creating a distance algorithm, which offers inherent power swing insensitivity instead of using a power swing blocking function, is achieved by applying the Δ-quantities of the αβ0-components of voltage and current. Beginning with the basics of the proposed distance algorithm up to a suitable relay logic, the all-important parts of the Δ21 relay are provided and discussed in this paper. Finally, a study case provides the platform for its performance evaluation.<br
Keywords: delta quantities; distance protection; Power swing; power system restoration; αβ0-components

Erdschlusserkennung basierend auf Künstlichen Neuronalen Netzen - Kordowich, Georg; Lorz, Tobias; Jaworski, Michael; Klumpp, Philipp; Perez Toro, Paula Andrea; Gaube, Sven; Kereit, Matthias; Böhme, Klaus; Nöth, Elmar; Jäger, Johann (12. VDE ETG-/FNN-Tutorial Schutz- und Leittechnik, 2022)
Erdschlüsse gehören zu den häufigsten Fehlern im Mittelspannungsnetz. Gleichzeitig ist insbesondere die Erkennung von hochohmigen Erdschlüssen eine der schwierigsten Aufgaben der Schutztechnik. Durch die zahlreichen Einflussparameter wie beispielsweise Fehlerursache, Bodenbeschaffenheit und Witterung auf Fehler- und Erdimpedanz können konventionelle Verfahren Erdschlüsse nicht in jedem Fall zuverlässig erkennen. In diesem Poster soll deshalb ein Konzept vorgestellt werden, das durch Verwendung von Künstlichen Neuronalen Netzen eine Ergänzung zu den etablierten Verfahren bilden soll. Durch ein Training sollen die Neuronalen Netze erlernen die komplexen Muster der Erdschlüsse zu erkennen und von anderen Schalthandlungen oder Fehlern abgrenzen können. Im Gegensatz zu konventionellen Schutzkonzepten, deren Erkennung meist von den Werten einzelner Parametern abhängt, sollen die Neuronalen Netze ein generisches Verständnis für die Muster entwickeln und so robuster und vielseitiger einsetzbar sein. Für die Generierung der Trainingsdaten ist ein möglichst akkurates Modell des entsprechenden Einsatzgebietes nötig. Mit diesem können automatisiert Simulationen durchgeführt, und Messdaten exportiert werden. Dabei werden verschiedene Fehlerorte und -zeitpunkte mit verschiedenen Parametern simuliert, um einen möglichst diversen Datensatz für ein robustes Training zu generieren. Die Messdaten aus den Simulationen werden anschließend für das Training der Neuronalen Netze verwendet. Um die Fehlererkennungsfähigkeit der Netze zu verifizieren, können diese anschließend mit Messdaten aus realen elektrischen Netzen validiert werde

Interactions of Protection Systems with Dynamic Phenomena in Islanded Distribution Grids during the Restoration Process - Jaworski, Michael; Jäger, Johann (2018 International Conference on Power System Technology, POWERCON 2018 - Proceedings, 2019)
Electromechanical dynamics are not only an issue on transmission system level. They also take place in distribution grids, in particular in islanded distribution grids, as long as there are at least two elements that form an oscillatory interaction with respect to their state variables. Considering this aspect is a key factor for developing restoration schemes, which focus on restoring electrical islands on the distribution level after a wide area blackout. This work answers the question of how the dynamic behavior of distribution islands differ from the well-known transmission system characteristic. Furthermore the necessity of migrating protection requirements like dynamic related short fault-clearing times or the implementation of power swing blocking functions on the protection relays in distribution systems is discussed.
CRIS-Team Scopus Importer:2020-02-21
Keywords: distribution grid; electromechanical dynamics; power system restoration; protection

Modelling of the Sympathetic Inrush Effect and its Impact on Protection Systems during Power System Restoration - Jaworski, Michael; Jäger, Johann (Protection, Automation & Control World Conference 2017 (PACWorld2017), 2017)

Protection Relay Behaviour during Power System Restoration - A Boundary based State Classification Approach - Jaworski, Michael; Jäger, Johann (The 13th IET International Conference on Developments in Power System Protection - DPSP, 2016)

Protection Security Assessment System in the Context of Power System Restoration - Hanika, Tobias; Jaworski, Michael; Jäger, Johann (IEEE PESS Power and Energy Student Summit, 2018)

Schutzsystemverhalten vor dem Hintergrund parameterbezogener Zustandsänderungen während des Netzwiederaufbaus - Jaworski, Michael; Jäger, Johann (9. ETG-/FNN-Tutorial Schutz- und Leittechnik, 2016)

Stabilitätsorientierte Netzauftrennung - Jaworski, Michael; Jäger, Johann (11. ETG-/FNN-Tutorial Schutz- und Leittechnik, 2020)

Sympathetic Transformer Inrush Detection and Relay blocking during Power System Restoration - Jaworski, Michael; Jäger, Johann (IEEE Transactions on Power Delivery, 2023)
A classic inrush current occurs during normal energization of reactive grid elements like transformers. It can simulate short-circuit currents. Hence inrush currents have to be detected and protection relays need to be blocked for avoiding their overfunction. Conventional detection criteria are the 2^nd harmonic content and some kind of current waveform analysis. A classic inrush can evolve into a sympathetic inrush event, if the energization of a single transformers drives other transformers into magnetic saturation. The risk of facing a sympathetic inrush current is particularly high during a power system restoration process. Its characteristic waveform differs from the classic inrush. While the classic inrush has unipolar current peaks, the sympathetic inrush is characterized by bipolar peaks. The conventional detection criteria tend to fail in this case. This paper proposes a new approach to detect sympathetic transformer inrush currents. The approach includes the detection of classic inrush currents as well as the distinction against short-circuit currents for ensuring the relay blocking. First it introduces the basic physical mechanism behind the evolution of a classic to a sympathetic inrush. The higher risk of facing a sympathetic inrush during the restoration process is shown by the physical mechanism as well. The proposed detection method is then introduced in detail. Three new differentiation criteria will be applied and merged together to a final decision. The paper closes with practical lab tests of the new approach on simulated sympathetic and measured classic inrush currents. All lab tests showed good results and promise a practical implementation in the grid.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Circuit faults; Inrush current; inrush current patterns; inrush feature extraction; Magnetic hysteresis; power system restoration; protective relaying; relay blocking; Saturation magnetization; Surge protection; transformer sympathetic inrush; Transformers; Voltage

System Integrity Protection by Orbital Grid-forming Mode for VSC - Lorz, Tobias; Jaworski, Michael; Jäger, Johann (16th International Conference on Developments in Power System Protection (DPSP 2022), 2022)
The primary challenge is to develop a protective function that utilises a VSC for fulfilling this task of dynamic system stabilization. In consequence, the protection function is realized in form of a converter control scheme that enables the VSC's operation in grid-forming mode (OGM) alongside with the synchronous generator. The Orbital Grid-forming mode OGM offers current limitation without a separate control-loop and even without measuring the current. Furthermore, it enables the VSC to stabilize electromechanical dynamics of synchronous machines by obtaining a maximum angular deviation between its internal voltage and their rotors. This means a generator cannot lose synchronism to the VSC and its rotor experiences a floating anchorpoint, which hinders its acceleration or deceleration until the dynamic excursion of the machine is over.
CRIS-Team Scopus Importer:2024-12-16
Keywords: GRID-FORMING; POWER SYSTEM RESTORATION; ROTOR ANGLE STABILITY; SYSTEM INTEGRITY PROTECTION

The Proactive Overload Protection System – An Approach to Avoid Cascading Line Tripping - Jaworski, Michael; Jäger, Johann; Retterath, M (7th International Conference on Advanced Power System Automation and Protection (APAP2017), 2017)